EV Markets: A Comparative Analysis between India, Nigeria, and Indonesia - Shree, Vandana; Edeh, Dr. Friday Ogbu; Sin, Dr. Liem Gai; Pandey, Dr. Rudresh; Tiwari, Swarn; Onukele, Amarachi; Gupta, Himanshu Kumar; K A, Farzan; Tiwari, Ganesh; Triana, Andra Aprillia Ayu; Alzahri, MHD. Daffa (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2024)
In this study, we present a nuanced comparative evaluation of the Electric Vehicle (EV) landscapes in India, Nigeria, and Indonesia — three emerging economies with divergent socio economic and infrastructural profiles. Our objective is to explain the multifaceted determinants underpinning EV adoption and growth within these nations. India, showcasing a more mature EV ecosystem, has witnessed accelerated growth propelled by encouraging governmental strategies, fiscal incentives, and an evolving charging framework. In contrast, Nigeria's embryonic EV sector grapples with infrastructural impediments and fiscal challenges. Indonesia has abundant natural resources, but demand for electric vehicles in Indonesia is still low so the infrastructure for vehicle charging stations is still in the development stage. Through an indepth scrutiny of consumer predilections, acquisition impediments, and state led initiatives, we delineate the idiosyncratic challenges and prospects inherent to each milieu. Our exploration further delves into the cultural, economic, and policy driven catalysts sculpting the EV milieu in these territories. The insights gleaned from this investigation serve as a pivotal reference for policymakers, industry aficionados, and financial proponents aiming to decode the intricate dynamics of the EV market within these variegated settings. Furthermore, the comparative paradigm employed augments the overarching comprehension of global EV assimilation patterns.